Impact assessment of the Strategic Planning performance in Shared U-space volumes - Juan José Ramos González; Zhiqiang Liu; Jose Luis Muñoz-Gamarra; Enric Pastor; Cristina Barrado (European Journal of Transport and Infrastructure Research)
This work analyses how the different U-space service providers (USSPs) managing a shared airspace volume will impact on the other’s performance. The paper demonstrates how the various strategic planning USSPs capabilities, ranging from procedures and policies, trajectory representation, as well as the deconflicting strategies, impact on the use of this common resource in terms of effective airspace capacity. The paper brings to practice the concept of Reasonable Time to React by proposing a planning timeline with common milestones for the implementation of the required authorization procedures prior to the flight. The paper analyses how these milestones impact on the effective airspace capacity. Also, the First-Come First-Served planning policy is compared with respect to a more efficient batch planning policy, where flight plan batches are processed to mitigate the potential conflicts existing at the strategic phase.  Furthermore, the paper discusses how the capabilities supported by the USSP to represent the trajectory and its associated uncertainty will be also key to optimize the use the airspace. Based on a CORUS-XUAM VLD scenario, a simulation analysis will assess how the USSPs’ capabilities to manage flight planning activities impact on the effective occupation of airspace, jeopardizing in some cases not just the own performance but also that of other airspace users.